Screening of Onion (Allium cepa L.) Genotypes for Waterlogging Tolerance - Gedam, Pranjali A.; Shirsat, Dhananjay V.; Arunachalam, Thangasamy; Ghosh, Sourav; Gawande, Suresh J.; Mahajan, Vijay; Gupta, Amar Jeet; Singh, Major (Frontiers in Plant Science, 2022)
Onion production is severely affected by waterlogging conditions, which are created due to heavy rainfall. Hence, the identification of waterlogging tolerant onion genotypes is crucial for increasing onion production. In the present study, hundred distinct onion genotypes were screened for waterlogging tolerance under artificial conditions by using the phenotypic approach in monsoon season 2017. Based on plant survival and recovery, and change in bulb weight, we identified 19 tolerant, 27 intermediate tolerant and 54 highly sensitive onion genotypes. The tolerant genotypes exhibited higher plant survival, better recovery and bulb size, whereas sensitive genotypes exhibited higher plant mortality, poor recovery, and small bulb size under waterlogging condition. Furthermore, a subset of 12 contrasting genotypes was selected for field trials during monsoon season 2018 and 2019. Results revealed that considerable variation in the morphological, physiological and yield characteristics were observed across the genotypes under stress condition. Waterlogging-tolerant genotypes namely Acc. 1666, Acc. 1622, W-355, W-208, KH-M-2 and RGP-5 exhibited higher plant height, leaf number, leaf area, leaf length, chlorophyll content, membrane stability index, pyruvic acid, antioxidant content, and bulb yield than sensitive genotypes under stress condition. Furthermore, the principal component analysis biplot revealed a strong association of leaf number, leaf area, chlorophyll content, membrane stability index, and bulb yield with tolerant genotypes under stress conditions. The study indicated that the waterlogging-tolerant onion genotypes with promising stress adaptive traits can be used in plant breeding programs for the developing waterlogging–tolerant onion varieties